The Histone Demethylase JMJD2A Modulates the Induction of Hypertrophy Markers in iPSC-Derived Cardiomyocytes - Rosales, Wendy; Lizcano, Fernando (Frontiers in Genetics, 2018)
The development of cardiovascular pathologies is partly attributed to epigenetic causes, including histone methylation, which appears to be an important marker in hearts that develop cardiac hypertrophy. Previous studies showed that the histone demethylase JMJD2A can regulate the hypertrophic process in murine cardiomyocytes. However, the influence of JMJD2A on cardiac hypertrophy in a human cardiomyocyte model is still poorly understood. In the present study, cardiomyocytes derived from human induced pluripotent stem cells (iPSCs) were used. Hypertrophy was induced by angiotensin II and endothelin-1 (ET-1), and transfections were performed to overexpress JMJD2A and for small interfering RNA (siRNA)-induced silencing of JMJD2A. Gene expression analyses were determined using RT-PCR and Western blot. The expression levels of B-type natriuretic peptide (BNP), natriuretic peptide A (ANP) and beta myosin heavy chain (β-MHC) were increased by nearly 2–10-fold with ET-1 compared with the control. However, a higher level of JMJD2A and UTX was detected, whereas the level of JMJD2C was lower. When cardiomyocytes were transiently transfected with JMJD2A, an increase close to 150% in BNP was observed, and this increase was greater after treatment with ET-1. To verify the specificity of JMJD2A activity, a knockdown was performed by means of siRNA-JMJD2A, which led to a significant reduction in BNP. The involvement of JMJD2A suggests that histone-specific modifications are associated with genes encoding proteins that are actively transcribed during the hypertrophy process. Since BNP is closely related to JMJD2A expression, we suggest that there could be a direct influence of JMJD2A on the expression of BNP. These results may be studied further to reduce cardiac hypertrophy via the regulation of epigenetic modifiers.